2019
DOI: 10.1021/acs.jafc.9b01203
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Inception of a Triterpenoid Astrakurkurol, as a Cytotoxic Molecule on Human Hepatocellular Carcinoma Cells, Hep3B

Abstract: Mushrooms are customary influential sources of pharmaceutically active metabolites. Usually lanostane-type triterpenoids from mushrooms had prospective for cancer disease treatments. Recently, a triterpenoid, astrakurkurol obtained from the fresh basidiocarps of the edible mushroom Astraeus hygrometricus, drew attention as a new cytotoxic therapeutic. The structural stability of this triterpenoid had been established with the amalgamation of density functional theory (DFT) calculations and study of single-crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The pellet was fixed with chilled 70% (v/v) ethanol and stored at 4°C for at least 24 hr. Cells were then resuspended in PBS containing propidium iodide (PI; a concentration of 20 μg/ml) and RNaseA (a concentration of 20 μg/ml) to stain DNA for 15 min (Nandi et al., 2019). Cells were then subjected to flow cytometer (BD accuri c6 plus, San Diego, CA), and the fraction of cells at each cell cycle was quantified with BD FACS Suite software.…”
Section: Methodsmentioning
confidence: 99%
“…The pellet was fixed with chilled 70% (v/v) ethanol and stored at 4°C for at least 24 hr. Cells were then resuspended in PBS containing propidium iodide (PI; a concentration of 20 μg/ml) and RNaseA (a concentration of 20 μg/ml) to stain DNA for 15 min (Nandi et al., 2019). Cells were then subjected to flow cytometer (BD accuri c6 plus, San Diego, CA), and the fraction of cells at each cell cycle was quantified with BD FACS Suite software.…”
Section: Methodsmentioning
confidence: 99%
“…Astrakurkurol, a triterpenoid extracted from fresh basidiocarps of the edible mushroom Astraeus hygrometricus was found to have anti-proliferative properties [50]. Astraeus hygrometricus has various health benefits such as anticancer, antidiabetic, and antioxidant properties [107][108].…”
Section: Astrakurkurolmentioning
confidence: 99%
“…Astraeus hygrometricus has various health benefits such as anticancer, antidiabetic, and antioxidant properties [107][108]. Nandi and colleagues [50] demonstrated that astrakurkurol can act as a cytotoxic drug. It was found to induce apoptosis in hepatocarcinoma cell line (Hep3B) and arrest cell cycle at the G0/G1 phase.…”
Section: Astrakurkurolmentioning
confidence: 99%
“…A549 cells were grown 85%–90% confluency in a 6‐well plate and scratch assay was carried out according to our previous description 20 . Samples were treated with different concentrations (0, 10.3, 20.6, and 30.9 μM) of astrakurkurol.…”
Section: Materials and Experimental Assaysmentioning
confidence: 99%
“…The helical structure of astrakurkurol ignites further interest into the role of helicity in anticancer activity. Moreover, concerning the anticancer efficacy of astrakurkurol, its part in the induction of apoptosis has been previously reported in liver cancer cells 20 . In our present study, we have tried to inspect the effect of astrakurkurol on apoptosis and/or autophagy and metastasis in lung adenocarcinoma (A549) cells, as the effect of autophagy and apoptosis has never been tested upon it so far with astrakurkurol.…”
Section: Introductionmentioning
confidence: 97%